2021
DOI: 10.1002/cti2.1326
|View full text |Cite
|
Sign up to set email alerts
|

Rapid whole‐blood assay to detect SARS‐CoV‐2‐specific memory T‐cell immunity following a single dose of AstraZeneca ChAdOx1‐S COVID‐19 vaccine

Abstract: Objectives With the ongoing emergence of SARS‐CoV‐2 variants and potential to evade vaccine‐induced neutralisation, understanding the magnitude and breadth of vaccine‐induced T‐cell immunity will be critical for the ongoing optimisation of vaccine approaches. Strategies that provide a rapid and easily translatable means of assessing virus‐specific T‐cell responses provide an opportunity to monitor the impact of vaccine rollouts in the community. In this study, we assessed whether our recently deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Plasma IL-2 was also an excellent biomarker for distinguishing vaccinated and unvaccinated individuals. These observations are in line with findings from Bertoletti and colleagues (22) and Smith and colleagues (23), among others, who also observed that IL-2 and IFN-g provided the most accurate readout of whole-blood based assays.…”
Section: Discussionsupporting
confidence: 89%
“…Plasma IL-2 was also an excellent biomarker for distinguishing vaccinated and unvaccinated individuals. These observations are in line with findings from Bertoletti and colleagues (22) and Smith and colleagues (23), among others, who also observed that IL-2 and IFN-g provided the most accurate readout of whole-blood based assays.…”
Section: Discussionsupporting
confidence: 89%
“…All these cases presented with a clinical picture of nephrotic syndrome that started up to 15 days after the first dose of the vaccine. The fairly short period from vaccination to presentation could be attributed to cytokine release by activated T-cells, as the ChAdOx1 vaccine has been shown to induce a robust T-cell response in most individuals ( 195 ). However, as the reported cases were limited, a definite conclusion could not be drawn.…”
Section: Autoimmune Adverse Events Following Immunization and Their C...mentioning
confidence: 99%
“…Considering the crucial role of T cell-mediated immunity during SARS-CoV-2 infection, it is imperative to understand the T cell response during COVID-19 vaccination. A replication-deficient simian adenoviral vector-based vaccine, ChAdOx1 nCoV-19 (AZD1222), has been shown to induce discrete clusters of populations of lymphocyte ( 70 ). These clusters were identified as Ki-67 + as proliferating population and CD69 + as activated population for both CD4 + and CD8 + T cells.…”
Section: Lymphocyte Response Against Covid-19-vaccinated Individualsmentioning
confidence: 99%